Minor Universality / Universalité mineure Rethinking Humanity After Western Universalism / Penser l'humanité après l'universalisme occidental - Messling, Markus; Tinius, Jonas (Beyond Universalism / Partager l'universel, 2023)
In times of relativism - marked by the critique of Western universalism on the one hand, and resurgent identitarian and neo-nationalistic claims to identity on the other, this volume tracks the development and relevance of cultural and social practices that posit forms of minor universality, asking: Where and how do contemporary practices open up concrete settings so as to create experiences, reflections and agencies of a shared humanity?